MicroRNA-155 Promotes the Directional Migration of Resident Smooth Muscle Progenitor Cells by Regulating Monocyte Chemoattractant Protein 1 in Transplant Arteriosclerosis. Issue 6 (June 2016) - Sun, Yuan; Wang, Ke; Ye, Ping; Wu, Jie; Ren, Lingyun; Zhang, Anchen; Huang, Xiaofan; Deng, Peng; Wu, Chuangyan; Yue, Zhang; Chen, Zhaolei; Ding, Xiangchao; et al.
Abstract : Objective—: Smooth muscle–like cells are major cell components of transplant arteriosclerosis lesions. This study investigated the origin of the smooth muscle–like cells, the mechanisms responsible for their accumulation in the neointima, and the factors that drive these processes. Approach and Results—: A murine aortic transplantation model was established by transplanting miR-155 −/− bone marrow cells into miR-155 +/+ mice. MicroRNA-155 was found to play a functional role in the transplant arteriosclerosis. Moreover, we found that the nonbone marrow–derived progenitor cells with markers of both early differentiated smooth muscles and stem cells in the allograft adventitia were smooth muscle progenitor cells. Purified smooth muscle progenitor cells expressed a mature smooth muscle cell marker when induced by platelet-derived growth factor-BB in vitro. In vivo, these cells could migrate into the intima from the adventitia and could contribute to the neointimal hyperplasia. The loss of microRNA-155 in bone marrow–derived cells decreased the concentration gradient of monocyte chemoattractant protein 1 between the intima and the adventitia of the allografts, which reduced the migration of smooth muscle progenitor cells from the adventitia into the neointima. Conclusions—: This study demonstrated that microRNA-155 promoted the directional migration of smooth muscle progenitor cells from the adventitia by regulating the monocyte chemoattractant protein 1 concentration gradient, which aggravated transplant arteriosclerosis. Abstract : Supplemental Digital Content is available in the text.